Economic Study of a Braced Multi-Story Steel Frame - Williams, James B.; Galambos, Theodore V. (Engineering Journal, 1968)
A braced frame is a steel skeleton in which the forces due to lateral load and the sway-induced second order moments are resisted by shear walls or bracing specifically designed for this purpose. Rigid framing in such frames is not designed to resist lateral forces and serves only to decrease the size of the beams. It is intended in this paper to describe the design and the cost analysis of a braced steel frame with both rigid framing and simple framing, and to determine how much the economy of using continuous girders is offset by the added cost of heavier columns and moment connections required for the girders.